Article Review: Biological Control of Aphids Using the Natural Predator Lady Beetle (Menochilus sexmaculatus) on Chili Plants - Pramesti, Meylita Filia; Amelia, Silfina Fara; Arista, Sekar Putri; Haryanto, Azika Saputri; Soesanto, Loekas (Jurnal Biologi Tropis, 2026)
Chili production is frequently hampered by Aphis sp. infestations, necessitating eco-friendly biological control alternatives. Although the predator Menochilus sexmaculatus shows potential, previous researchers explicitly noted a lack of synthesized data quantifying its specific predation rates and predator-to-prey ratios. This study aims to evaluate the biocontrol efficacy of M. sexmaculatus against aphids on chili. Following PRISMA protocols, a Systematic Literature Review (SLR) used thematic analysis on articles (2017–2026) from Scopus, Google Scholar, and ScienceDirect, using keywords "Menochilus sexmaculatus", "aphids", and "chili" under strict inclusion criteria. Synthesized findings indicate that M. sexmaculatus exhibits substantial predation efficacy, marked by high consumption rates and rapid population suppression. Higher predator-to-prey ratios significantly accelerate pest suppression without disrupting ecological dynamics. In conclusion, M. sexmaculatus serves as a potent agent to reduce aphid population density in sustainable agriculture. Integrating predator conservation into pest management is recommended, while future research should focus on mass production techniques.